1979
DOI: 10.1902/jop.1979.50.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Damaging Effects of Toothbrush Bristle End Form on Gingiva

Abstract: The ability of two different toothbrush bristle ends to produce traumatic gingival abrasion was assessed in a double blind study of 15 male and 15 female young adults. Brushing was performed in a circular fashion using a modified Bass Technique. An apparatus allowing continuous visual feedback of the average brushing force permitted a degree of standardization of the system. The upper left canine and bicuspid area had to be brushed for 30 seconds with cut toothbrush bristles (CP) and with round ended toothbrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 6 publications
2
78
0
2
Order By: Relevance
“…T he exposure of root surfaces by gingival recession may be due to several etiologic factors, including periodontal disease, 1,2 mechanical forces such as faulty toothbrushing, 3 iatrogenic factors like orthodontic movement, 4,5 faulty restorations, 6 and anatomical factors such as tooth malposition and frenum pull. 7,8 Gingival recession seldom results in tooth loss.…”
mentioning
confidence: 99%
“…T he exposure of root surfaces by gingival recession may be due to several etiologic factors, including periodontal disease, 1,2 mechanical forces such as faulty toothbrushing, 3 iatrogenic factors like orthodontic movement, 4,5 faulty restorations, 6 and anatomical factors such as tooth malposition and frenum pull. 7,8 Gingival recession seldom results in tooth loss.…”
mentioning
confidence: 99%
“…It is known that generic bristled tooth brushes can induce gingival abrasion [24], especially if the bristles are hard and not rounded [25,26]. This may occur even in those who use little force while brushing [27].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The literature has shown that brushes with medium and stiff bristles remove more plaque than soft brushes, although they cause greater gingival abrasion. 9, 10,11,12,13 In addition, medium-hard toothbrushes were found to be a significant risk factor for the incidence of gingival fissures.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,16 Soft brushes with tapered or conical filaments were recently introduced. The diameter of the body of these filaments is similar to that of the filaments of a conventional soft brush, but the diameter of the filament tip is significantly smaller.…”
Section: Introductionmentioning
confidence: 99%